2020
DOI: 10.1128/jvi.01164-20
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Defensins Enhance Japanese Encephalitis Virus Infection by Facilitating Virus Adsorption and Entry within the Mosquito

Abstract: Japanese encephalitis virus (JEV) is a viral zoonosis that can cause viral encephalitis, death and disability. Although the Culex mosquito is the primary vector of JEV, little is known about JEV transmission by this kind of mosquito. Here, we found that mosquito defensin facilitated the adsorption of JEV on target cells via the defensin/lipoprotein receptor-related protein 2 (LRP2) axis. Mosquito defensin bound the ED III domain of the viral envelope (E) protein and directly mediated efficient virus adsorption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that the AMP defensin, which is one of the crucial immune effectors in insects [ 154 ], plays an important role in facilitating JEV infection and potential transmission in mosquitoes. An initial study by Liu et al [ 155 ] showed that mosquito defensins ( Culex pipiens pallens defensin A and Aedes albopictus defensin C) facilitate the adsorption of JEV to target cells by binding to a specific part of the viral envelope protein of JEV. Moreover, under natural conditions, the local infection of the midgut leads to rapid upregulation and extracellular secretion of defensins [ 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the AMP defensin, which is one of the crucial immune effectors in insects [ 154 ], plays an important role in facilitating JEV infection and potential transmission in mosquitoes. An initial study by Liu et al [ 155 ] showed that mosquito defensins ( Culex pipiens pallens defensin A and Aedes albopictus defensin C) facilitate the adsorption of JEV to target cells by binding to a specific part of the viral envelope protein of JEV. Moreover, under natural conditions, the local infection of the midgut leads to rapid upregulation and extracellular secretion of defensins [ 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Female Cx . pipiens pallens were used to investigate the role of mosquito defensins [ 96 , 167 ] and of a C-type lectin protein [ 168 ] on the JEV infection documenting substantial amounts of JEV in the salivary glands (10 dpi). Doi and colleagues showed that the subtype Cx .…”
Section: Resultsmentioning
confidence: 99%
“…A large number of viruses from diverse families has been shown to induce the expression of NF-κB-regulated genes, and in many cases components within NF-κB signalling pathways have also been shown to mediate antiviral effects. Interestingly, viruses differ in their susceptibility to different NF-κB pathways, and there are also examples of NF-κB-regulated effectors acting in a pro-viral fashion [83, 85]. A major outstanding question regards the underlying molecular basis for these differences, some of which likely stem from differences in the ways in which viruses interact with their natural hosts compared to non-natural virus-host combinations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some virus-specificity to the observed antiviral effects of A. aegypti NF-κB pathways [83], with conflicting reports on whether NF-κB pathways are antiviral (or not) against ZIKV [84]. Furthermore, Japanese encephalitis virus infection of Culex pipiens pallens and A. albopictus -derived C6/36 cells appears to be enhanced by Defensins, which bind JEV virions and increase viral adsorption to the cells [85]. In contrast, Rel2 and TRAF knockdown in C. quinquefasciatus and Hsu cells resulted in enhanced WNV replication [69].…”
Section: Antiviral Role Of Nf-κb Signalling Pathways In Mosquitoesmentioning
confidence: 99%